Human Papillomavirus Distribution in Invasive Cervical Carcinoma in Sub-Saharan Africa: Could HIV Explain the Differences? - Ndiaye, Cathy; Alemany, Laia; Ndiaye, Nafissatou; Kamate, Bakarou; Odida, Michael; Banjo, Kunbi; Klaustermeier, Jo Ellen; Clavero, Omar; Trottier, Helen; Sanjose, Silvia de (Tropical Medicine & International Health, 2012)
To describe human papillomavirus (HPV) distribution in invasive cervical carcinoma (ICC) from Mali and Senegal and to compare type-specific relative contribution among sub-Saharan African (SSA) countries. A multicentric study was conducted to collect paraffin-embedded blocks of ICC. Polymerase chain reaction, DNA enzyme immunoassay and line probe assay were performed for HPV detection and genotyping. Data from SSA (Mozambique, Nigeria and Uganda) and 35 other countries were compared. One hundred and sixty-four ICC cases from Mali and Senegal were tested from which 138 were positive (adjusted prevalence = 86.8%; 95% CI = 79.7–91.7%). HPV16 and HPV18 accounted for 57.2% of infections and HPV45 for 16.7%. In SSA countries, HPV16 was less frequent than in the rest of the world (49.4%vs. 62.6%; P < 0.0001) but HPV18 and HPV45 were two times more frequent (19.3%vs. 9.4%; P < 0.0001 and 10.3%vs. 5.6%; P < 0.0001, respectively). There was an ecological correlation between HIV prevalence and the increase of HPV18 and the decrease of HPV45 in ICC in SSA (P = 0.037 for both). HPV16/18/45 accounted for two-thirds of the HPV types found in invasive cervical cancer in Mali and Senegal. Our results suggest that HIV may play a role in the underlying HPV18 and HPV45 contribution to cervical cancer, but further studies are needed to confirm this correlation.
Keywords: Human papillomavirus; invasive cervical carcinoma; HIV